Effects of formative assessment on academic performance in physical education among high school students - Moreira Barre , Fresia Aracely; León Vélez, Ruth María; López Carvajal, Guadalupe del Rosario; Castro Ponce, Nelly Elena (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
Assessment in physical education at the high school level should not be limited to assigning a grade at the end of the term. This study aimed to analyze the effects of using formative assessment tools on the academic performance of 480 students aged 14–19 years. This applied study used a quantitative, quasi-experimental design to compare two groups: one with formative assessment tools and one with traditional methods, measuring their impact on academic performance. Participants were divided into an experimental group and a control group. The intervention consisted of ten practical sessions using formative assessment tools, including rubrics, checklists, observation sheets, self-assessment, and peer-assessment. Results showed that the experimental group significantly improved their academic performance compared to the control group (p<0.05), demonstrating higher participation, effort, and engagement. The findings support that the implementation of formative assessment enhances not only academic performance but also student involvement in their own learning.